Binding of Silver(I) Ions by Alfalfa Biomass (Medicago Sativa): Batch PH, Time, Temperature, and Ionic Strength Studies - I. Herrera; J. L. Gardea-Torresdey; K. J. Tiemann; J. R. Peralta-Videa; V. Armendariz; J. G. Parsons (Journal of Hazardous Substance Research, 2003)
In this study, the use of alfalfa biomass as a cost-effective and environmentally safe technique to recover Ag(I) ions from aqueous solutions is reported. This investigation consisted of batch pH profile, time, temperature, and ionic strength dependence studies. Results showed that alfalfa biomass presented the highest adsorption of Ag(I) ions in the pH range of 7 to 9 with a maximum adsorption capacity of 27.37 mg Ag•g-1 of dry biomass, evaluated with a solution of 32.4 ppm of Ag(I). Time and temperature studies demonstrated a stable adsorption of Ag(I) ions by the biomass during the first hour of exposure, with a small decrease in adsorption after this period. Temperature experiments showed that Ag(I) adsorption decreases significantly at 50 ºC as compared to 4ºC and 24 ºC. However, the differences between 4ºC and 24ºC are small. Ionic strength experiments showed that interfering ions (Na and Ca) reduce the adsorption capacity of the biomass. Results of this investigation showed that alfalfa biomass can be effectively used in the recovery process of silver ions from aqueous solutions.
Keywords: silver; phytofiltration; ion-exchange resins; alfalfa biomass